The Great Recession and Ethno-Racial Disparities in Access to Mortgage Credit. (3rd November 2020) - Loya, José; Flippen, Chenoa
Abstract: The mortgage industry has long been central to racially and ethnically stratified access to homeownership. Liberalized access to credit during the 1990s and early 2000s targeted subprime and other high-cost loans to individuals and communities of color. This article draws on annual data from the Home Mortgage Disclosure Act (HMDA) from 2004 through 2017 to assess short-term variation in racial and ethnic disparities in loan outcomes associated with the Great Recession. We show that, relative to the boom, this period is associated with a reduction in disparities in loan outcomes between non-Hispanic whites and Asians on the one hand and blacks and Latinos on the other. This is particularly true for the disproportionate channeling of black and Latino applicants into high-cost loans, and in communities with higher minority concentrations. As the economy and access to credit improved, particularly after 2011, black and Latino over-representation in high-cost loans began to rebound, though ethno-racial disparities in loan rejection continued well below levels observed during the boom years. The return of inequality in high-cost lending is particularly troubling in light of the sharp drop in minority applications. Implications for ethno-racial stratification are discussed.